KETAHANAN LIMA JENIS KAYU TERHADAP SERANGAN DELAPAN JENIS JAMUR PELAPUK - Sihati Suprapti; Esti Rini Satiti; Lisna Efiyant; Djarwanto (BRIN Publishing, 2021)
Lesser-known wood originating from rain-forests is an alternative raw material for the national timber industry.Optimizing this wood group’s utilisation requires information on its resistance to the decaying fungus attack of eachwood species used. This research is studying the resistance of five wood species from West Kalimantan, and the rusttest was carried out on the metal embedded in heartwood and exposed to fungus using the Kolle-flask method. NaOH’swood-solubility analysis referred to ASTM D-1110-84’s Standard. Results revealed that Albizia sp. and Syzygiumsp. belonged to resistant woods (class II); Santiria sp. and Lithocarpus ewyckii belonged to moderately-resistant(class III); while Xanthophyllum excelsum belonged to not-resistant (class IV). The greatest weight loss occurredat sapwood of Xanthophyllum excelsum being exposed to Pycnoporus sanguineus. Average weight loss atheartwood (with class II) was lower than that at sapwood (class III). The greatest weight loss of woods embedded byscrews occurred at screwed Syzygium sp. then exposed to Polyporus sp. The average weight loss of screwed woods wasgreater than that of unscrewed woods. Meanwhile, the highest weight loss of screws occurred at Xanthophyllumexcelsum, then at Syzygium sp., exposed to Polyporus arcularius. The greatest weight of screw-rust powder wasachieved at Syzygium sp. exposed to Polyporus arcularius. Five fungi species exhibited moderate capability, whilethree species afforded low capability in decaying woods. The effect of decaying fungi on corroding screws was entirely low.